The relationship between pre-service kindergarten teachers’ professional identification and career adaptability: A chain mediation model - Qiao, Tianqi; Song, Zhanmei; Huang, Jie; Yan, Jingfeng; Zhang, Xueying; Wang, Yixuan; Liu, Cong; Wang, Yang (Frontiers in Psychology, 2022)
Background The healthy development of preschool education requires the support of stable and high-quality preschool teachers. However, there are still many deficiencies in preschool teachers in China at present. For pre-service kindergarten teachers, it is very significant to improve their career adaptability and enter professional positions smoothly. Numerous studies have found the effect of professional identification on the career adaptability of pre-service kindergarten teachers, but few studies have explored the potential influencing mechanisms among variables. On the basis of previous studies, this study explores the chain mediating effect of teacher efficacy and self-leadership on the relationship between professional identification and career adaptability of pre-service kindergarten teachers. Methods Three hundred eighty-eight participants were recruited from two schools in Zhejiang Province. After screening, 377 questionnaires for pre-service kindergarten teachers were used for data analysis. The questionnaire included self-reported demographic information, professional identification, teacher efficacy, self-leadership, and career adaptability. We collected information on variables by using PISNS, TSE, RSLQ, and CFI, and analyzed the data using SPSS. Results (1) Professional identification and career adaptability have a significant positive correlation. (2) The influence of occupational identification on the career adaptability of pre-service kindergarten teachers was carried out in three different ways: professional identification → teacher efficacy → career adaptability, professional identification → self-leadership → career adaptability, and professional identification → teacher efficacy → self-leadership → career adaptability. Conclusion Teacher efficacy and self-leadership may mediate the relationship between professional identification and career adaptability of pre-service kindergarten teachers. This study highlighted the complexity of the link between preschool teachers’ professional identification and career adaptability. The paper also discussed the limitations and implications of this study.